2013
DOI: 10.13080/z-a.2013.100.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of primary soil tillage on soil weed seed bank and weed incidence in a cereal-grass crop rotation

Abstract: A field experiment was carried out at Vėžaičiai Branch of Lithuanian Research Centre for Agriculture and Forestry during the period 2008-2011. The study was aimed to determine the effects of various soil tillage methods: deep ploughing (20-25 cm), shallow ploughing (10-12 cm), shallow ploughless tillage (8-10 cm) and soil fertility improvement measures (plant residues, plant residues + straw, green manure 1 st cut + straw, green manure 2 nd cut + straw, farmyard manure 40 t ha -1 + straw) on the soil weed seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In our experiment, shallowly incorporating white mustard (as a green manure) encouraged the spread of weeds of wet, nitrogen-rich and very nitrogen-rich soils. Previous research has shown that reduced tillage increases the incidence of the weed species of nitrogen-rich and very rich soils (Cirsium arvense L., Elytrygia repens L., Poa annua L., Stellaria media (L.) Vill., Tripleurospermum perforatum (Mérat) M. Laínz) in spring and winter cereal crops [24,25]. Studies carried out in Lithuania show that in the direct drilling system, the total density of weeds before herbicide application was 21.0% higher and before harvesting was 42.0% higher when compared with conventional ploughing [26].…”
Section: The Effect Of Different Tillage Systems and Crop Residue In The Soil On Weed Community Compositionmentioning
confidence: 99%
“…In our experiment, shallowly incorporating white mustard (as a green manure) encouraged the spread of weeds of wet, nitrogen-rich and very nitrogen-rich soils. Previous research has shown that reduced tillage increases the incidence of the weed species of nitrogen-rich and very rich soils (Cirsium arvense L., Elytrygia repens L., Poa annua L., Stellaria media (L.) Vill., Tripleurospermum perforatum (Mérat) M. Laínz) in spring and winter cereal crops [24,25]. Studies carried out in Lithuania show that in the direct drilling system, the total density of weeds before herbicide application was 21.0% higher and before harvesting was 42.0% higher when compared with conventional ploughing [26].…”
Section: The Effect Of Different Tillage Systems and Crop Residue In The Soil On Weed Community Compositionmentioning
confidence: 99%
“…Analysis of the size and composition of the weed seedbank in the soil can provide information on the past and present weed populations and forecast any future weed problems (Auffret, Cousins, 2011). Changes in the soil weed seed reserves depend on soil tillage, crop rotation, and weed control (Auškalnienė, Auškalnis, 2009;Skuodienė et al, 2013). Weed community composition in the surface (0-15 cm) layer seems more influenced by tillage system than by crop rotation (Barberi, Lo Cascio, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In slightly acidic West Lithuania's Dystric Albeluvisol with low content of organic matter, primary soil tillage had a significant impact on the weed incidence in the crops of the rotation. The highest number of weeds and their dry mass in winter wheat and spring rape stands was determined by applying shallow ploughless tillage, in spring barley -shallow ploughing and in the sward of red clover -deep and shallow ploughing (Skuodienė et al, 2013). Assessing the primary ploughless soil tillage influence on the weed incidence in crops in West Lithuania's weatherbeaten soils it was determined that it had the greatest impact on perennial weeds whose population changes were more consistent than those of the annual weeds because of reduced soil tillage.…”
Section: Introductionmentioning
confidence: 99%